Clinical approach to lung diseases in HIV-infected patients (review) - I. B. Viktorova; V. N. Zimina; S. Yu. Degtyareva; A. V. Kravtchenko (Журнал инфектологии)
The review presents literature data on therapeutic and diagnostic management of pulmonary diseases in HIV-infected patients. The article provides different practical approaches in the diagnosis of HIV-associated lung lesions and the spectrum of probable diseases, depending on the degree of immunodeficiency and the severity of clinical manifestations. The reference clinical signs of the most common opportunistic diseases with possible lung involvement are presented.The literature review highlights the feasibility of accurate etiological and invasive diagnosis of lung lesions in different clinical settings, as well as the need to designate various options of empirical  antimicrobial therapy. The features of antimicrobial therapy and, in particular, the use of fluoroquinolones during the differential diagnosis of pulmonary lesions in HIV infection are discussed. The difficulties of verifying of HIV-associated lung diseases indicate the need of unified therapeutic and diagnostic approaches for use by various physicians (general practitioners, pulmonologists andphthisiologists).